N-P-O co-doped high performance 3D graphene prepared through red phosphorous-assisted "cutting-thin" technique: A universal synthesis and multifunctional applications. (October 2016) - Zhao, Yufeng; Huang, Shifei; Xia, Meirong; Rehman, Sarish; Mu, Shichun; Kou, Zongkui; Zhang, Zhi; Chen, Zhaoyang; Gao, Faming; Hou, Yanglong
Abstract: Large scale production of three dimensional (3D) graphene materials with high density and low degree of defects stands for the main challenge hindering their practical applications. Herein, we report a universal and readily scalable strategy to produce an N-P-O co-doped free standing 3D graphene through a one-pot red phosphorus-assisted "cutting-thin" technique. The solid carbon precursor is gradually exfoliated through the slowly released gases (e.g. pH3, H2, CO2 ) and metallic K during the reaction, which allows the formation of dominant amount nanopores, and ensures the high density of the products. The as-produced graphene exhibits continuously 3D hierarchical porous (3D-HPG) structure with good quality (ID /IG =0.4, I2D /IG =0.65). Density functional theory (DFT) calculations indicate the N-P-O co-doping can significantly enhance the charge delocalization with benefited electrochemical activity. The 3D-HPG is directly utilized as the supercapacitor electrode and a metal free catalyst for oxygen reduction reaction (ORR), offering ultrahigh specific capacitance of 426 F g −1 (424 F cm −3 ), as well as excellent catalytic performance. The assembled all-solid-state cell exhibits both high gravimetric (25.3 W h kg −1 ) and volumetric (25.2 W h L −1 ) energy density, which are among the highest values of the state-of-art carbon only supercapacitors. Remarkably, this "cutting-thin" strategy is applicable to variable carbon sources. Graphical abstract: An N-P-O co-doped free standing 3D graphene is synthesized through a one-pot red phosphorus-assisted "cutting-thin" technique. The material is directly utilized as the supercapacitor electrode and a metal free catalyst for oxygen reduction reaction (ORR), offering ultrahigh specific capacitance, as well as excellent catalytic performance. Remarkably, this "cutting-thin" strategy is applicable to various carbon sources. Highlights: An N-P-O co-doped 3D graphene is produced through a novel "cutting-thin" strategy. This "cutting-thin" strategy is applicable to variable carbon sources. The 3D graphene exhibits ultrahigh specific capacitance of 426 F g −1 (424 F cm −3 ). The 3D graphene can be directly utilized as an excellent metal free ORR catalyst.